Destination in the Southern Part of Iloilo, Philippines - Pelasol, Ma. Rhona J.; Tayoba, Michelle Anne T.; Mondero, Elna; Jugado, Khristy; Lahaylahay, Christopher (JPAIR Multidisciplinary Research, 2012)
The Philippines is endowed with abundant natural tourist attractions. One of the provinces in the Philippines is Iloilo wherein the town of Igbaras can be found. Igbaras is considered as one of the leading tourist destinations in the province due to its bountiful hidden attractions. Igcabugao is home to Igbaras' several beauty spots such as Igcabugao Cave, Lapusan Cave, with an underground river, and Guiritsan Falls. This study was conducted to determine the potential of Igcabugao as a tourist destination in the southern part of Iloilo. Videos and pictures of Igcabugao were used by the researchers in focused group discussion conducted among tourism students of the different colleges and universities in Iloilo City. Qualitative thematic analysis was used to analyze the findings of the study. Findings revealed that Igcabugao have a lot of natural attractions that it could be developed as a potential tourist destination. It concluded that Igcabugao has the elements of a successful tourist destination. The cooperation of residents, local government and the tourism sector is a key to plan for and develop Igcabugao as a tourist destination. Recommendations, among others, were centered on the drafting of a Sustainable Tourism Development Plan for Igcabugao.
Keywords: Tourist destination; tourism management; Guiritsan Falls; Igcabugao Cave; Lapusan Cave